2016
DOI: 10.1371/journal.pone.0167936
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial-Mesenchymal Transition in Vascular Calcification of Ins2Akita/+ Mice

Abstract: Endothelial-mesenchymal transition (EndMT) drives endothelium to contribute to normal development and disease processes. Here, we report that EndMTs occur in the diabetic endothelium of Ins2Akita/wt mouse, and show that induction of sex determining region Y-box 2 (Sox2) is a mediator of excess BMP signaling that results in activation of EndMTs and increased vascular calcification. We also find an induction of a complex of serine proteases in the diabetic endothelium, required for the up-regulation of Sox2. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 55 publications
3
26
0
1
Order By: Relevance
“…Previous studies have shown that ECs with mesenchymal and stem cell-like characteristics contribute to cerebral cavernous malformation, atherosclerosis, and the human genetic disorder fibrodysplasia ossificans progressiva (14,18,34). Moreover, ECs undergoing mesenchymal differentiation have been traced in studies of vascular calcification, where ECs gain multipotency and contribute osteoprogenitors to the calcifying process (17,22,35,36). Here, we show the emergence of mesenchymal stem cell markers in the endothelium of cerebral AVMs, which indicate a change in the endothelial fate through EndMTs.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have shown that ECs with mesenchymal and stem cell-like characteristics contribute to cerebral cavernous malformation, atherosclerosis, and the human genetic disorder fibrodysplasia ossificans progressiva (14,18,34). Moreover, ECs undergoing mesenchymal differentiation have been traced in studies of vascular calcification, where ECs gain multipotency and contribute osteoprogenitors to the calcifying process (17,22,35,36). Here, we show the emergence of mesenchymal stem cell markers in the endothelium of cerebral AVMs, which indicate a change in the endothelial fate through EndMTs.…”
Section: Discussionsupporting
confidence: 57%
“…We next aimed to validate our findings in vivo using an animal model of atherosclerosis. The contribution of EndMT to vascular calcification and atherosclerosis has been investigated in different animal models, including LDLR −/− , ApoE‐deficient, and Ins Akita mice . The ApoE3Leiden mice constitute a valuable model of diet‐induced atherosclerosis with a human‐like lipoprotein profile when fed a high‐fat diet .…”
Section: Resultsmentioning
confidence: 99%
“…The identification of patients at increased risk of acute coronary events associated with vascular calcification, who may benefit from intensified preventative measures and for monitoring therapeutic efficacy, is a major ongoing challenge . Recent publications have suggested that ECs directly contribute to vascular calcification through EndMT . We investigated the interplay between inflammatory cytokines and BMPs, a subfamily of the TGF‐β family, in ECs.…”
Section: Discussionmentioning
confidence: 99%
“…Guihard et al showed that the CD31 + CD45 ‐ sorted cells from the aorta of those mice exhibited increased expression of multipotent factors, including Sox‐2 , and that the endothelial specific deletion of Sox‐2 prevented aortic calcification. Also in this model, the pharmacological inhibition of serine proteases using diisopropyl fluorophosphate (DFP) blocked aortic calcification (Guihard et al, ).…”
Section: Endmt In Cardiovascular Disordersmentioning
confidence: 98%